Beyond User Decline: Investigating the Effects of Social Presence and the Dual Role of Social Connectedness in Sustaining Engagement on Social Networking Platforms - Vidayana, Vidayana; Burhanudin, Burhanudin; Lokaadingroho, Indrabudhi; Mansuan, Melki Sadekh (Register: Jurnal Ilmiah Teknologi Sistem Informasi, 2024)
Social media platforms are currently grappling with unforeseen difficulties that have hindered their expansion. Previous studies have disclosed that Facebook, one of the most prominent social media sites, has encountered a reduction in its user base. Similarly, other social media platforms have also reported a substantial decline in user numbers and engagement levels, indicating a significant downturn in their popularity. The primary objective of this research is to gain a more comprehensive understanding of the role played by the social presence in human-computer-mediated interactions, specifically in the context of social media. Data from 473 college students from their second to tenth semesters were collected through an online survey. Amos 25 was utilized to test the constructs of the variables of social presence, social connectedness, attitude, and intention to continue using social media. The Hayes Macro Process version 3.5 was used to test the proposed model. The results showed that social connectedness (Con) moderates the effect of social presence and attitude on user intention to continue using social networks. This result extends the body of research on human-computer-mediated interactions by uncovering the role of connectedness in human-computer-mediated interactions and technology adoption.